Living MedsCheck: Learning how to deliver MedsCheck in community practice in Ontario. (January 2013) - Grindrod, Kelly; Sanghera, Niki; Rahmaan, Israa; Roy, Meghna; Tritt, Michael
Objective: To share the experiences of graduating students as they learn to deliver a new medication review service in community pharmacies in Ontario, Canada. Practice description: Four graduating pharmacy students volunteered in different community pharmacies to learn how to navigate a new provincial program called MedsCheck, which pays pharmacists to do medication reviews. Each student selected his or her own practice site, including 2 independent community pharmacies, a grocery store chain pharmacy and a hospital outpatient pharmacy. Practice innovation: To help the students learn to deliver the new MedsCheck services, a faculty mentor met with them on a weekly basis. To reflect on doing MedsChecks in the "real world" and to elicit feedback from the online community, each student blogged about his or her experiences. Results: All 4 students felt that peer mentoring improved their ability to deliver MedsCheck services. They also identified a number of barriers to delivering the MedsChecks and helped each other try to overcome the barriers. Conclusion: MedsCheck is a new service in Ontario and is not easily implemented in the current pharmacy model of practice. Peer mentoring is a helpful way to share successes and overcome barriers to delivery. Can Pharm J 2013;146:33-38.